Editorial - KLEIN, Hans (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
Dear colleague Stelian Tofană, On 2 April 2023 you turned 65. On this occasion the friends of this journal from near and far, colleagues, New Testament scholars from Romania and abroad greet you and sincerely wish you God’s blessing and much strength to continue your work in the field of New Testament studies. In a manner visible to many, you have dedicated all your intellectual and spiritual energy to the service of biblical studies, to the dissemination of the results of New Testament research to many interested listeners and readers. After obtaining the degree in Orthodox theology from the Babeș-Bolyai University in Cluj in 1984, you entered the service of the Church as priest in the university city and its vicinity. You have been serving at the Orthodox cathedral of this city since 1998 and thus biblical interpretation has reached a large audience through your sermons. At the same time, soon after completing your studies, you took on a teaching position, first as a substitute professor at the Orthodox Theological Seminary (1988–1990), then as an assistant at the Orthodox Theological Institute (1990–1994), as a lecturer at the Orthodox Theological Faculty of the Babeș-Bolyai University (1994–1996), as a senior lecturer (1996–1998) and professor of New Testament (since 1998) at the same university. In this capacity you participated in the 1998 meeting of the East-West Symposium on Biblical Theology organised by the Eastern European Liaison Committee of the Studiorum Novi Testamenti Societas at the Neamț Monastery. Soon thereafter you were elected as a member of the SNTS. Joining the society gave you the opportunity to convey the Orthodox approach to New Testament interpretation to many colleagues from all over the world and you contributed thereby to a shared understanding of this part of our Bible.